HUBUNGAN AKTIVITAS FISIK DAN TINGKAT STRES DENGAN KEJADIAN DISMENORE PRIMER PADA REMAJA PUTRI DI SMK KESEHATAN KOTA TANGERANG - Enggar Pradiasa Mardika Candi; Febi Ratnasari; H. AYG Wibisono (Nusantara Hasana Journal, 2023)
Background: Dysmenorrhea is one of the most common disorders experienced by women. Dysmenorrhea usually occurs before menstruation. Dysmenorrhea is usually in the form of pain in the lower abdomen and pelvis which can cause pain in the back and thighs. Objective: To analyze the relationship between physical activity and stress levels with the incidence of primary dysmenorrhea in young women at SMK Kesehatan Kota Tangerang. Research Design: This type of research uses a quantitative method with a cross sectional methodology. Sample technique: Using a purposive sample technique with the Lemeshow formula. With a total sample of 384. Data analysis: Skewness Kurtosis Normality Test, Univariate Analysis, and Chi-Square Liked Lihood Bivariate Analysis. Results: The Chi-Square Liked Lihood test of physical activity with the incidence of dysmenorrhea obtained a p-value of 0.030 <0.05, so it can be concluded that there is a relationship between physical activity and the incidence of dysmenorrhea in young women at SMK Kesehatan Kota Tangerang. The results of the Chi-Square Liked Lihood Test for stress levels with the incidence of dysmenorrhea obtained a p-value of 0.032 <0.05, so it can be concluded that there is a relationship between stress levels and the incidence of dysmenorrhea in young women at SMK Kesehatan Kota Tangerang. Conclusion: From this study, there is a significant relationship between physical activity and stress levels with the incidence of dysmenorrhea in young women at SMK Kesehatan Kota Tangerang.